Sistem Pengaturan Lahan Parkir Mobil Pada Mall Surabaya Town Square ( Sutos) - Apriyanto, Samuel Christian; Sukmaaji, Anjik; Soebijono, Tony (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
Abstract: First of all, the development of technology, which has been developed at this time, has encouraged the acceleration in several fields; especially in the field of information technology. Associated to the requirement for information that has increased, commonly, parking management use a ticket to sign in and out of motor vehicles that has been parked. Along with the difficulties often encountered by users of parking services such as difficulty on finding an empty parking location, parking services where users have to revolve - around looking for an empty parking lot, and certainly not to get a parking space, in addition to the parking service users often forget where previously parked vehicle. The purpose of the present study was to identify a result to combine and develop the existing parking system environments by utilizing the parking area sufficient support for the implementation of the parking system settings. In conclusion, through a system of information that has been created, will make it more manageable for the user services and parking services manager, furthermore the aim of the thesis is expected to be one of the experimental developments in parking management.Â Keywords: Parking management, Parking services and Â The parking system.